Biodiversity assessment of Indian mangroves using in situ observations and remotely sensed data. Issue 4 (1st October 2020) - Kripa, M. K.; Lele, Nikhil; Panda, Muktipada; Kumar Das, Susanta; Nivas A, Hari; Divakaran, Niranjan; Sawant, Apoorva; Naik-Gaonkar, Sankrita; Pattnaik, A. K.; Samal, R. N.; Thangaradjou, T.; Saravanakumar, A.; et al.
ABSTRACT: Mangroves are one of the most productive coastal ecosystems, which act as natural barriers against natural calamities such as cyclones, tide upsurges and tsunamis. Mangrove ecosystems provide natural habitat for a wide variety of flora and fauna, whilst the economic contribution by mangroves for tourism, fisheries and other natural resources is also of paramount importance. This study focusses on the biodiversity of four major regions of Indian mangroves, namely, Bhitarkanika (Odisha), Pichavaram (Tamil Nadu), Chorao Islands (Goa) and Porlob Jig (Andaman and Nicobar Islands). The study aims to monitor the present status of mangroves in Southern and Eastern coasts of India, with the synergistic use of optical and SAR data. The aerial extents of all the Dominant vegetation spatial maps generated revealed that the Bhitarkanika mangroves had the largest extent (14425 ha) among the four mangrove regions. The second largest area recorded was by the Porlob Jig mangroves of the Andaman and Nicobar Islands (9972 ha), followed by the Pichavaram mangroves (788 ha) and the mangroves of Chorao Islands of Goa (603 ha). Decision makers, for taking the necessary conservation and management actions to protect these fragile, vital habitats can ultimately use this data. Key policy insights: This paper provides an insight into the major mangrove species of India. It gives a detailed account of the varying mangrove biodiversity in the Eastern and Western coast of India. The prevalence of various kinds of mangroves from different ecosystems were documented. Among these, Rhizophora annamalayana specious was found indigenously in Tamil Nadu.